An Experimental Investigation of R134a Clathrates with Liquid Additives - Gulzar, Hafiz M. Ahmad (2016)
A Master of Science thesis in Mechanical Engineering by Hafiz M. Ahmad Gulzar entitled, "An Experimental Investigation of R134a Clathrates with Liquid Additives," submitted in September 2016. Thesis advisor is Dr. Saad A. Ahmed and thesis co-advisor is Dr. Mohamed Gadalla. Soft and hard copy available.